COVID‐19 Knowledge and Behavior Change among High School Students in Semi‐Rural Georgia. (16th May 2021) - Campbell, Katherine; Weingart, Rachel; Ashta, Jasleen; Cronin, Thomas; Gazmararian, Julie
ABSTRACT: BACKGROUND: Many schools transitioned online to reduce viral spread and promote social distancing amid the COVID‐19 pandemic. Remote learning may impact health behaviors and coping strategies among adolescents, including reduced physical activity and increased screen time. Social media and peers provide information about the pandemic to adolescents and may influence prevention behaviors. This study aims to assess adolescent knowledge and information about COVID‐19, determine students' behavior change, and identify sources students turn to for information on the pandemic. METHODS: Students from 2 high schools in semi‐rural Georgia participated in a cross‐sectional online survey in March 2020 (N = 761). RESULTS: Common sources for COVID‐19 news were peers (80%) and social media (58%). Few adolescents (3%) indicated that teenagers were at higher risk of severe illness due to COVID‐19. Responses reveal adolescents understand social distancing and many are participating in prevention behaviors, including handwashing (87%) and staying at home as much as possible (87%). Most respondents reported increases in screen time outside of class (82%). CONCLUSIONS: Findings suggest adolescents are obtaining COVID‐19 knowledge from various sources, including social media, with varying degrees of implementation of prevention practices. Increases in screen time and reduced physical activity may impact long‐term health among adolescents.